Ultra Micro Financing (UMi) and Trade Labor: Impacts on GRDP in the Large Trade and Retail Business Field of Bangka Belitung Islands Province (2017-2022) - Febriyani, Lintri; Nugroho, Ari Agung; Leksono, Binar Kukuh; Maheswara, Perpetua Westri; Saputra, Hermawan (Master of Management Department, Faculty of Economics and Business, Universitas Bangka Belitung, 2023)
Ultra Micro Financing (UMi) aims to provide fast and accessible financing for ultra-micro businesses, fostering government-financed entrepreneurs. UMi Financing’s dominance can influence labor absorption and Gross Regional Domestic Product (GRDP) in the Large Trade and Retail Business Field. This research analyzes the impact of UMi Financing and Trade Labor Absorption on Trade GRDP in Bangka Belitung Islands Province during 2017-2022. Path analysis measures the direct and indirect effects of UMi Financing on Trade GRDP. The findings reveal that UMi financing affects trade and GRDP in Bangka Belitung Islands Province. However, UMi Financing does not directly influence Trade GRDP when mediated by labor. Moreover, UMi Financing and Trade Labor do not significantly impact the GDP of Large Trade and Retail. Limited labor absorption in the trade sector may be attributed to the relatively small capital or financing provided by UMi. Additionally, the absorption of labor in the trade sector does not significantly affect Trade GRDP in the province, as the gross value added in the Large Trade and Retail sectors is influenced by people’s purchasing power, which is still highly dependent on commodity price fluctuations. To bolster GDP growth in the large trade and retail sectors, the government can encourage the distribution of UMi Financing. UMi Financing Distributors should intensify assistance to scale up debtor’s businesses. Diversifying UMi distribution to sectors beyond wholesale and retail trade can also be explored.